'That's Not Very Manly': Debating Japanese Masculinities on Terrace House. Issue 1 (2nd January 2021) - Nelson, Lindsay
ABSTRACT: On the Japanese television show franchise Terrace House, six people live in a large home together and cameras record their interactions, with the key addition of a group of comedians and television personalities who watch the show together and comment on it. In its ongoing discussions of which housemates and behaviors are the most 'manly', Terrace House offers a window into contemporary debates about masculinities in Japan. In examining in-show incidents and commentary related to the housemates' sexuality, aggression, passivity, maturity, and attitudes toward money and labor, we begin to see how certain norms surrounding masculinities in Japan are shifting (and how some remain static). Focusing on the 2017–2019 iteration of the show, 'Opening New Doors', this paper examines how the interactions of Terrace House 's young housemates, the reactions of the show's (mostly older) commentators, the responses of fans, and the show's editing and structural choices reveal conflicting ideas about what it means to be 'manly' (as well as to be a responsible adult) in contemporary Japan.